2012
DOI: 10.5395/rde.2012.37.3.149
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Root ZX in teeth with simulated root perforation in the presence of gel or liquid type endodontic irrigant

Abstract: ObjectivesTo evaluate the accuracy of the Root ZX in teeth with simulated root perforation in the presence of gel or liquid type endodontic irrigants, such as saline, 5.25% sodium hypochlorite (NaOCl), 2% chlorhexidine liquid, 2% chlorhexidine gel, and RC-Prep, and also to determine the electrical conductivities of these endodontic irrigants.Materials and MethodsA root perforation was simulated on twenty freshly extracted teeth by means of a small perforation made on the proximal surface of the root at 4 mm fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 24 publications
(30 reference statements)
4
27
0
2
Order By: Relevance
“…Previous studies showed that CHX group was closest to the actual length. [ 31 ] This finding was confirmed in this study. CHX group showed shortest distance to the apex than that of NaOCl group for both the apex locator measurements.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies showed that CHX group was closest to the actual length. [ 31 ] This finding was confirmed in this study. CHX group showed shortest distance to the apex than that of NaOCl group for both the apex locator measurements.…”
Section: Discussionsupporting
confidence: 88%
“…[21] However, according to Shin et al ., electrical conductivity of CHX was much lower than other liquid type of irrigants. [20] This can be presumed to be the main contributing factor in our study.…”
Section: Discussionmentioning
confidence: 84%
“…According to Shin et al ., electrical conductivity of tap water is 100–1000 μS/cm and 1% NaOCl is 1,72,420 μS/cm, and such differences in the electrical conductivity among different irrigating solutions are said to affect the determination of the working length. [20]…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with the above-mentioned studies. Many studies have used a ± 0.5 mm error range to assess the accuracy of the EALs 22,23 , and others have relied on a range of ±1.0 mm. 11,24 Measurements within these tolerances were considered accurate and clinically acceptable in the present study because the relation between the rubber stop and the reference point, the rubber stop and the caliper, or the file tip and the caliper was difficult to control visually.…”
Section: Tepeklinikmentioning
confidence: 99%